Frequency of overtime and consecutive games and their impact on injury rate in the national hockey league (NHL) - Rosenberg, S. I.; Baker, H. P.; Rizzi, A.; Terry, M. A.; Tjong, V. K. (The Physician and Sportsmedicine, 2021)
Objectives Ice hockey is a high-intensity contact sport that places athletes at an elevated risk for injury relative to other sports. The purpose of the current study was to analyze factors contributing to fatigue and decreased recovery time and their associations with injury incidence among professional athletes in the National Hockey League (NHL).